Mutual Effects of Environment and Urbanization: A Sociological Assessment - Mohammad Taghi Sheykhi (Annals of Environmental Science and Toxicology - Peertechz Publications, 2020)
The article explores how urban areas are widely affecting the environment with special reference to the developing countries. Urbanization as the outcome of population growth in rural areas, decline of agricultural productivity and migration is creating more economic activities and dynamics in towns and cities leading to environmental issues and challenges. It is well observed in terms of transportation, solid waste, air, water, shortage of green space etc. in urban areas. In that, different age groups including children and the elderly people are badly affected. While urbanization affects society, urban inhabitants are constantly increasing due to improved transportation, more social network accessibility, higher literacy rate of young population, higher socio-economic expectations, change in lifestyles etc. However, density of population in cities has widely and negatively culminated in urban environmental catastrophes; some phenomenon which will affect next generations as well. Objective: As one of the main functions of sociology is to find social problems, the current paper tries to do that. Urbanization is increasingly and primarily affecting the environment. Destruction of environment and creation of the built environment, itself creating social, economic, health and many more problems, is one of the objectives of the research. If the issue is controlled, decline of other problems will follow, and consequently steps toward a safe and secure society will be taken. The analytics of the paper will on average reflect how urbanization is destroying societies as a whole. Similarly, sociology usually proposes ethical resolutions. The author also made use of the sources possible to collect the data necessary. Note, English not being the first language of the author, is expected to be average. One of the topics very related to sociology is urbanization. Population proves the objective relationship between urbanization with the environment. Any change in population in quantitative or qualitative terms, while impacting urbanization, it affects the environment too. Nowadays, the factor of population, and as a result, increasing urbanization has endangered the environment. Therefore, governments and the decision-making systems need to make proper decisions to keep the environment safe and clean. Environmental safety widely impacts the population; in that, babies, mothers and the aging people find more security. Probably, most of the problems and challenges of the 21st century are the results of the 20th century problems which were not administratively and politically observed and paid attention to, sufficiently. Weaknesses and shortcomings pertaining to policy-making have contributed to the 1st century challenges as stemmed from population, urbanization and the environment. Those are the key points to be explored in the present article.